PRODUCT INNOVATION IN IMPROVING COOPERATIVE PERFORMANCE - Zuhriyah, Nur Azizah (Yayasan Education and Social Center, 2024)
Study This aiming For analyze influence innovation product to performance cooperative . In environment growing business​ competitive , cooperative sued For Keep going innovate to be able to survive and thrive . Research This use method quantitative with Partial Least Square (PLS) approach to analyze connection between innovation products and performance cooperatives . Research results show that innovation product influential significant to performance cooperative with contribution by 46.7%, with a t-statistic of 3.726 which is greater than big from standard 1.96 and p-value 0.000, which indicates strong relationship​ between second variables . Findings This confirm that active cooperative​ in do innovation , good from aspect quality , design , and Variants product , capable increase satisfaction members and power compete in the market. However , the challenges main in implementation innovation is lack of source Power competent human resources , difficulties in implementation of ideas, as well as low courage in take risk . Therefore that , cooperative need increase human resources capacity , utilizing digital technology , as well as build synergy with various stakeholders interests.With the right innovation strategy , cooperatives can develop more good , improve welfare members , as well as contribute more big in economy national